To study the incidence of gestational diabetes mellitus and risk factors associated with GDM - Anand, Maxima; Anand, Manan; Mahajan, Devinder Singh (International Journal of Advances in Medicine, 2017)
Background: Diabetes is estimated to complicate 2-5% of all pregnancies of which 90% of those are detected during pregnancy i.e. gestational diabetes mellitus (GDM) and the rest are overt or pregestational i.e. either Type 1 or Type 2. According to ADA, approximately 7% of all pregnancies are complicated by GDM resulting in more than 2,00,000 cases annually. The aim was to study the incidence of GDM among pregnant women between 24 to 28 weeks of gestation, to evaluate and compare the occurrence of risk factors e.g.; family history of diabetes, prematurity, history of foetal loss and congenital anomaly associated with diabetes in pregnancy. Methods: 50gm of glucose, glucose challenge test (GCT) was given to women coming for antenatal check-up between 24 to 28 weeks of gestation irrespective of presence or absence of risk factors for GDM.1 hour glucose levels were checked. Patients with glucose levels more than 130mg/dl were subjected to 100gm of oral glucose tolerance test (OGTT) according to Carpenter and Coustan modification of the National Diabetes Data. Data was compiled and statistically analysed. Results: In this study it was observed that 20 (women had raised GCT, 11 (5.3%) women developed GDM out of 206 women. All GDM patients have one or more risk factors. Age >25 years (63.6%) fetal loss (36.3%), BMI (33.3%) are common risk factors followed by family history of diabetes (27.3%). Conclusions: Family history of diabetes and past history of congenital anomalies are statistically significant in GDM group as compared to non GDM.